ESSENCE OF INTERNATIONAL TECHNICAL ASSISTANCE - Lutsenko , Anhelina (Theory and Practice of Public Administration, 2019)
The paper examines issues related to the definition of the concept of International Technical Assistance. As it is known one of the elements of modern international relations system is a set of mechanisms of help to the developing countries in their social economic growth. One of such mechanism is international technical assistance (ITA), which is aimed to facilitate the development of countries-recipients. The goal of the study was to analyze the current state on available researches of the concept of international technical assistance and to justify the need to improve the system of legal regulation of this phenomenon.While researching the problem was identified: there is no unified definition of the “international technical assistance”. It should be noted that international legal acts and scientific literature refer to various terms of this phenomenon: “external aid”, “technical assistance”, “international technical assistance”, “assistance” etc. It indicates that the approach of the definition of this concept is not formed. It was found out that defining the content of such phenomenon as international technical assistance is an interdisciplinary problem that concerns such fields as public administration, economics, law, international relations.Special attention is paid to the problem of the absence of a special law, which will regulate all aspects of attracting and using international technical assistance in Ukraine. Nowadays issues connected with the attraction of international technical assistance are regulated by the Act of Cabinet of Ministers 15.02.2002 №153 “On Creation of a Unified System for Involvement, Use and Monitoring of International Technical Assistance”. The analysis of this legal act showed that the concept of international technical assistance and a mechanism of its attraction and use are not fully described. In its turn, it causes a lot of legal misunderstandings. That’s why it is suggested that Ukraine currently needs a full-fledged law on the international technical assistance that would legally define this concept and streamline the mechanisms of attracting and using the ITA.